Tanggung jawab Sosial Korporasi dan Hak-Hak Masyarakat Hukum Adat - - Afrizal (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
This article scrutinizes the implementation of Corporate Social Responsibility (CSR) concept on the recognition of indigenous society’s rights over agrarian resources. It is argued that the concept is relevant to study forms of social relation between corporations and indigenous societies. Publication about that is little. Indigenous societies across Indonesia insist that they have rights over agrarian sources within their customary territory and the rights are recognized by the Indonesian state as well as international bodies. Academicians only pay attention to the government’s responsibility to recognize and respect the indigenous society’s rights. It is contended that from the concept of CSR a corporation is responsible for recognizing and respecting indigenous societies’ rights over agrarian sources, but this article demonstrates that realization of indigenous community’s rights by corporations is dependent upon pressure from indigenous communities rather than coporations’ initiative.